Delamination and recycling of Archaean crust caused by gravitational instabilities - Johnson, Tim; Brown, M.; Kaus, B.; VanTongeren, J. (Nature Publishing Group, Macmillan Publishers Ltd, 2014)
Mantle temperatures during the Archaean eon were higher than today. As a consequence, the primary crust formed at the time is thought to have been extensive, thick and magnesium rich, and underlain by a highly residual mantle1. However, the preserved volume of this crust today is low, implying that much of it was recycled back into the mantle2. Furthermore, Archaean crust exposed today is composed mostly of tonalite–trondhjemite–granodiorite, indicative of a hydrated, low-magnesium basalt source3, suggesting that they were not directly generated from a magnesium-rich primary crust. Here we present thermodynamic calculations that indicate that the stable mineral assemblages expected to form at the base of a 45-km-thick, fully hydrated and anhydrous magnesium-rich crust are denser than the underlying, complementary residual mantle. We use two-dimensional geodynamic models to show that the base of magmatically over-thickened magnesium-rich crust, whether fully hydrated or anhydrous, would have been gravitationally unstable at mantle temperatures greater than 1,500–1,550?°C. The dense crust would drip down into the mantle, generating a return flow of asthenospheric mantle that melts to create more primary crust. Continued melting of over-thickened and dripping magnesium-rich crust, combined with fractionation of primary magmas, may have produced the hydrated magnesium-poor basalts necessary to source tonalite–trondhjemite–granodiorite melts. The residues of these processes, with an ultramafic composition, must now reside in the mantle.